Sobre nazis y nazismo en la cultura argentina - KLICH, Ignacio comp. (HISPAMERICA, 2002)
Otros descriptores: América Latina.Colaboradores: OTEIZA, Enrique; SOSNOWSKI, Saúl; LANUS, Juan Archivaldo; DEGIOVANNI, Fernando; SENKMAN, Leonardo; BUCHRUCKER, Cristian; SABSAY, Daniel; POCHAK, Andrea; BARBERO, María Inés; ROUGIER, Marcelo; ROMERO, Luis Alberto; TATO, María Inés